A novel SYNE1 gene mutation in a Chinese family of Emery-Dreifuss muscular dystrophy-like - Zuzhi Chen; Zhixia Ren; Wenli Mei; Qiankun Ma; Yingying Shi; Yuanxing Zhang; Shujian Li; Li Xiang; Jiewen Zhang (BMC, 2017)
Abstract Background In the present study, a novel mutation in exon 46 at codon 2304 (G2304R) of the SYNE1 gene is described in a Chinese family (proband, mother, and sister) with Emery-Dreifuss muscular dystrophy-like, which clinically manifests as muscle weakness, muscle atrophy, joint contracture, and without significant cardiac abnormalities. Methods Clinical examination and neuroimaging of the captured target region and high-throughput sequencing were performed in a family of four generations. Muscle changes were evaluated using magnetic resonance imaging and muscle biopsies. Results Target region capture sequencing yielded a novel missense mutation in codon 2304 (G2304R), which is a heterozygous A to G point mutation at position 6910 (c.6910A > G) in exon 46 of SYNE1 leading to a glycine-to-arginine substitution (p.Gly2304Arg). The results were also identified by Sanger sequencing in three family members but not in the other three unaffected family members and 100 control subjects. Conclusions This mutation is probably pathogenic and is the first of its kind reported in a familial Emery-Dreifuss muscular dystrophy-like.